Community Satisfaction Level toward Chief of Sector Police Transformation Leadership in the Development of Bhabinkamtibmas in Bireuen - Adli Adli; Diding Nurdin; Cepi Triatna; Muhammad Rezeki Muamar (Universitas Pendidikan Indonesia, 2022)
The aim of this study is to see community satisfaction level toward chief of sector police transformation leadership in the develop-ment of Bhabinkamtibmas in the Bireun. This study used the subject of 86 Geuchik people in Bireun who were given an online questionnaire containing 8 (eight) positive statements about the main tasks of Bhabinkamtibmas. The results showed that community satisfaction level toward chief of sector police transfor-mation leadership in the development of Bhabinkamtibmas in the Bireun was very satisfied as many as 63 people (73%), quite satisfied 21 people (24%) and less satisfied 2 people (3%). So it can be concluded that the community is very satisfied with the transformational leadership of the chief of sector police in fostering Bhabinkamtibmas in Bireun. Transformational leadership is a leadership style that can influence the innovative behavior of team members or followers either directly or indirectly. Bhabinkamtib-mas is a member of the National Police who is tasked with building security and public order in villages/kelurahan/other names at the same level. Chief of sector police as the leader has the responsibility in fostering Bhabinkamtibmas. The leadership style of the Chief of sector police has the characteristics of transformational leadership in building the motivation of its members, which in this case is Bhabinkamtibmas.